The role of the perception of family environment in relation to body dissatisfaction, disordered eating and difficulties in close relationships - Gonçalves, Sónia (2020)
Purpose Invalidating childhood environments have been characterised as those in which caregivers do not validate a child's personal experiences and the communication of emotions is considered inappropriate, being either ignored or punished. The current study assessed the relationships among invalidating childhood environments, body dissatisfaction, disordered eating and difficulties in close relationships in a sample of college students. Methods In this study, 362 non-clinical participants with ages ranging from 17 to 25 years (M = 20.02, SD = 1.51) completed self-report measures. Results Difficulties in close relationships, body dissatisfaction and disordered eating were significantly higher in invalidating families than in validating families. Invalidating childhood environments were associated with higher body dissatisfaction and disordered eating, and both associations were mediated by difficulties in close relationships. Finally, body dissatisfaction mediates the effects of BMI and difficulties in close relationships on eating disorder symptoms. Conclusions Perceived experiences of invalidation in childhood may be associated with eating disorder symptomatology. In addition, difficulties in close relationships during adulthood possibly contribute to the emergence of eating disorder symptoms.